IMPLIKASI âIN SEARCH OF EXELLENCEâ DI INDONESIA (Potensio, 2014)
AbstractThere are eight points of basic principle for deference result excellent from the big business in America in long time that in take side to evident act, always near with customers, having otonomy and entrepreneurship, increasing productivity pass through HRD, increasing value in main business, always in the business who known, employ a little staff in high level and high dedication. This analysis for tracing about âin search of excellenceâ by Tom Peters in conection with business in Indonesia. This hypothesis very important to reciting in this analysis. There are conection in a manner evident interaction between America and Indonesia. Remembering that the both have the same system i.e. system open market and in market competitive structure.Â Key words: Implication âin search of excellenceâ in Indonesia.